2014
DOI: 10.1590/0103-8478cr20140030
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolics, flavonoids, tannins and antioxidant activity of lima beans conserved in a Brazilian Genebank

Abstract: The objective of this study was to characterize for the first time polyphenols and DPPH (2-diphenyl-1-picryhydrazyl radical) antioxidant activity in commonly cultivated accessions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…In general, polyphenol contents and antioxidant activity of pea seeds had a high linear correlation, which indicated that the phenolic compounds deactivate the free radicals or convert them into stable compounds (AGOSTINIC-COSTA et al, 2015). Furthermore, significant correlations were reported between seed color parameters and TPC, TFC, and antioxidant activity.…”
Section: Multivariate Correlation Analysismentioning
confidence: 92%
“…In general, polyphenol contents and antioxidant activity of pea seeds had a high linear correlation, which indicated that the phenolic compounds deactivate the free radicals or convert them into stable compounds (AGOSTINIC-COSTA et al, 2015). Furthermore, significant correlations were reported between seed color parameters and TPC, TFC, and antioxidant activity.…”
Section: Multivariate Correlation Analysismentioning
confidence: 92%
“…Identifi cation and quantifi cation of phenolic compounds in beans is important for developing successful new value--added bean-based products for new market opportunities in the functional food and nutraceutical industry and currently there is great interest in examining the phytochemical composition of legumes Chen et al, 2015;Agostini-Costa et al, 2015]. On the other hand, some researchers reported that phenolic compounds content and antioxidant activities of bean seeds were signifi cantly affected by cultivar [Oomah et al, 2005;Ramirez-Jiménez et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 gives the variations reported for phenolics in grain legumes. Among lima bean germplasm, there was 2–4-fold variation for phenols, except for one study that indicated a very high level (97-fold; Agostini-Costa et al, 2015 ). Ferulic acid was the most abundant, followed by p-coumaric and sinapic acids (Espinosa-Alonso et al, 2006 ; Luthria and Pastor-Corrales, 2006 ).…”
Section: Germplasm Mining For Variations In Phenylpropanoidsmentioning
confidence: 96%